1989
DOI: 10.1007/bf02544588
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipoproteins in dairy cows with naturally occurring severe fatty liver: Evidence of alteration in the distribution of apo A‐I‐containing lipoproteins

Abstract: The relationships between fatty liver in dairy cows and reduced levels of plasma lipoproteins, and particularly of low density lipoproteins (LDL), has been previously described. Since electrophoretic heterogeneity of ultracentrifugally isolated LDL (d, 1.006–1.063 g/ml) has been found, the exact nature of this reduction in cows with fatty liver was investigated. Lipoproteins from control and severely afflicted animals were isolated by ultracentrifugation and affinity chromatography on heparin‐Sepharose CL 6 B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Bovines, in particular, have low serum triglyceride and ape B levels and high cholesterol and apo A-I levels. In the present study, high levels of FFA were observed in fatty liver cows, which is in agreement with previous results (3,10). The early lactation post-partum period is of particular interest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bovines, in particular, have low serum triglyceride and ape B levels and high cholesterol and apo A-I levels. In the present study, high levels of FFA were observed in fatty liver cows, which is in agreement with previous results (3,10). The early lactation post-partum period is of particular interest.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies in our laboratory have shown that severe fatty liver is associated with a decrease and an alteration in the distribution of apo A-I-containlng lipoproteins (10). The possible origin of these modifications has already been discussed (10) and it could plausibly be explained as the result of reduced secretion of VLDL by the fiver.…”
Section: Discussionmentioning
confidence: 91%
“…[13]. The concentration of serum APO B-100 was reported to decrease in cattle when experimental fatty liver was produced and in naturally-occuring fatty liver [7,15]. In the present study, we measured the serum concentration of APO B-100 in cattle of varying ages, breeds and sex, maintained under normal field conditions.…”
mentioning
confidence: 94%
“…Compared with non-lactating or lactating pregnant cows, early lactating cows have higher serum NEFA concentrations and higher concentrations of TAG in their livers; moreover, they have very low serum concentrations of total cholesterol and apolipoproteins (63,64,69). It has been reported that plasma concentrations of low density lipoprotein (LDL) (70,84) and VLDL (84) are very low in cows which naturally develop fatty liver after parturition. In cows with hepatic lipidosis induced by the administration of ethionine, which inhibits hepatic protein synthesis, the concentration of liver TAG is very high, and the serum concentrations of VLDL and LDL are very low (79,109).…”
Section: Negative Energy Balance and Fatty Livermentioning
confidence: 99%